P860 Results from a combination of OX40 (PF-04518600) and 4–1BB (utomilumab) agonistic antibodies in melanoma and non-small cell lung cancer in a phase 1 dose expansion cohort. (15th April 2020) - Chiappori, Alberto; Thompson, John; Eskens, Fredericus; Spano, Jean-Philippe; Doi, Toshihiko; Hamid, Omid; Diab, Adi; Rizvi, Naiyer; Hu-Lieskovan, Siwen; Ros, Willeke; Thomas, Jacob; Forgie, Alison; et al.
Abstract : Background: PF-04518600 (PF-8600) and utomilumab (uto) are humanized agonist IgG2 monoclonal antibodies for the tumor necrosis factor superfamily receptors OX40 and 4-1BB, respectively. In a phase I dose escalation study (NCT02315066 ), this antibody combination was tolerable at all dose levels and induced responses in patients with melanoma resistant to immune checkpoint inhibitors. We report results from a dose expansion cohort of this study of patients with melanoma and non-small cell lung cancer (NSCLC) treated with PF-8600 (OX40 antibody) in combination with uto. Efficacy, safety, and the association of baseline and pharmacodynamic biomarkers with efficacy were examined. Methods: In this expansion cohort, patients with locally advanced/metastatic melanoma (n=10) and NSCLC (n=20) who progressed on prior anti-PD1/PD-L1 treatment and/or anti CTLA4 treatment (melanoma only) were enrolled. Patients received OX40 antibody 30 mg IV every 2wks in combination with uto 20 mg IV every 28d. Tumor assessments were performed every 8wks using RECIST1.1. Paired biopsy samples collected at baseline and 6wks were analyzed by immunohistochemistry and RNA sequencing to evaluate the pharmacodynamic effects of the OX40 antibody in combination with uto. Whole blood samples were collected longitudinally, from which DNA was extracted and submitted for high-throughput sequencing of the T cell receptor β-chain. Results: One patient with NSCLC achieved a confirmed and ongoing partial response lasting at least 6 months; Based on analyses of a subset of baseline biopsies, this patient's tumor had the lowest FOXP3 expression. A total of 7 (70%) melanoma patients and 7 (35%) NSCLC patients achieved a best overall response of stable disease (SD). The median duration of SD was 16.3 weeks (melanoma: 16.0 weeks; NSCLC: 24.1 weeks), for a disease control rate of 50%. Among patients with a defined response, paired biopsy analyses showed that the greatest increase in CD8 occurred in the NSCLC patient with the longest duration of stable disease. The most frequent treatment related adverse events (TRAEs) reported in ≥10% of patients were pruritis, anemia, fatigue, decreased appetite, and rash. Grade 3 TRAEs, rash and lymphocyte count decreased, were reported in 5 patients and a grade 4 TRAE of lipase increased (asymptomatic) was reported in 1 patient. Conclusions: The combination of PF-8600 and uto had a tolerable safety profile and demonstrated clinical benefit, including in an NSCLC patient who had progressed on anti-PD1 therapy and achieved a durable partial response. Further combinations with one or both of these immune costimulatory receptor agonist antibodies might enhance their efficacy. Acknowledgements: This study was funded by Pfizer Inc. Editorial support was provided by Chu Kong Liew, PhD, of Engage Scientific Solutions and was funded by Pfizer Inc. Trial Registration: ClinicalTrials. gov: NCT02315066 Ethics Approval: The study was approved by the institutional review board at each study center and conducted in accordance with the ethical principles of the Declaration of Helsinki.